Pengaruh GCG Dan Income Smoothing Terhadap Nilai Perusahaan Dengan CSR Sebagai Variabel Moderasi - Yohana Natalia; Rilla Gantino (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2025)
This study was conducted to analyze the influence of Good Corporate Governance and Income Smoothing on Firm Value, with Corporate Social Responsibility as a moderating variable, in mining sector companies within the metals and minerals sub-sector during the period 2021–2023. The population of this study consists of 87 samples from 29 companies over the 2021–2023 period, obtained using a saturated sampling method and financial statements sourced from the Indonesia Stock Exchange (IDX). In this study, Good Corporate Governance (GCG) is proxied by the Corporate Governance Perception Index (CGPI) and the 2021 KNKG disclosure standards. Income Smoothing is measured using the Eckel Index as a proxy. Corporate Social Responsibility (CSR) is measured using the CSR index as a proxy and the 2021 Global Reporting Initiative (GRI) as the reference for disclosure items. Firm Value is measured using the Price to Book Value (PBV) as its proxy. The analytical techniques used in this study include multiple regression analysis and Moderated Regression Analysis (MRA), using SPSS Statistics 25 software. The results show that Good Corporate Governance has a significant positive effect on Firm Value, while Income Smoothing has a significant negative effect on Firm Value. Corporate Social Responsibility does not have a significant effect, but it shows a positive direction toward Firm Value. Furthermore, Corporate Social Responsibility strengthens the effect of Good Corporate Governance on Firm Value and weakens the effect of Income Smoothing on Firm Value. This research was conducted to measure the effect of Corporate Governance, Income Smoothing practices, and Corporate Social Responsibility on firm value in the mining industry, specifically the metal and mineral subsector, listed on the Indonesia Stock Exchange (IDX) for the years 2021–2023.